Seismic Vulnerability Maps of Ratu Agung District, Bengkulu City, Indonesia - Lindung Zalbuin Mase (Institute of Research and Community Outreach - Petra Christian University, 2019)
During the 8.6 Mw Bengkulu-Mentawai Earthquake Ratu Agung District was identified as an impacted area. This paper aims to deliver the seismic vulnerability based on geophysical observation. This study was initiated by performing the ambient noise measurement to obtain the geophysical characteristic, such as amplification and predominant frequency. Furthermore, the vulnerability index analysis was performed from the geophysical information collected from the investigation. To observe the tendency of ground damage during the earthquake, ground damages analysis is also performed. All results are depicted into the microzonation maps. The results showed that the amplification and predominant frequency on site are generally ranging from 3 to 5 and 5 to 8 Hz, respectively. The seismic vulnerability index in study area is up to 10-3. The results showed that during the Bengkulu-Mentawai Earthquake, the investigated sites could be possible to undergo crack settlement which can trigger massive sand boiling in the study area.